PENGARUH KOMPENSASI DAN KEMAMPUAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. DUTA PALMA NUSANTARA DI KABUPATEN KUANTAN SINGINGI - Fadhillah, Muhammad; ', Marnis; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aims of this reseacrh is to examine the effect of compensation and employability on productivity. The population of this reseach is taken from employes of the production of PT. Duta Palma Nusantara. Accidental sampling method is used to get the samples, and from 405 peoples that we observed, we get 80 peoples as the samples. To analyze the data Multiple Linier Regression, F- test, and t- test analysis with using SPSS 17. The result shows that all variables simultaneously and significanly affected toward productivity in PT. Duta Palma Nusantara. The result shows t- test analysis indicates that compensation and employability that has significant effect on productivity. Suggestion of this research is a necessary balance between the compensation awarded by the company employee capabilities, management companies need to consider compensation to be applied, so that the salary system implemented based on the productivity of employees. The management company also needs to consider in order to observe the ability of management employees in the work stamina and health, especially for work in the plantation requires good stamina employees in order to increase productivity.Keywords : Compensation, Ability, and Work Productivity